2014
DOI: 10.1002/aic.14430
|View full text |Cite
|
Sign up to set email alerts
|

Control structure synthesis for operational optimization of mixed refrigerant processes for liquefied natural gas plant

Abstract: The best control structures for the energy optimizing control of propane precooled mixed refrigerant (C 3 MR) processes were examined. A first principles-based rigorous dynamic model was developed to analyze the steady-state and dynamic behaviors of the C 3 MR process. The steady-state optimality of the C 3 MR process was then examined in a whole operation space for exploring the feasibility of the energy optimizing control for possible control structures. As a result, the temperature difference (TD) between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…With a trial and error approach, the optimization of LNG processes can be achieved without using any special optimization algorithm. Reports ,, are available concerning optimized LNG processes obtained by modifying the structure and operating parameters without applying any deterministic or stochastic algorithms. However, to avoid confusion, in this study, we have focused on deterministic, stochastic, and KBO-based design optimization studies of LNG processes.…”
Section: Design Optimization Of Lng Processesmentioning
confidence: 99%
“…With a trial and error approach, the optimization of LNG processes can be achieved without using any special optimization algorithm. Reports ,, are available concerning optimized LNG processes obtained by modifying the structure and operating parameters without applying any deterministic or stochastic algorithms. However, to avoid confusion, in this study, we have focused on deterministic, stochastic, and KBO-based design optimization studies of LNG processes.…”
Section: Design Optimization Of Lng Processesmentioning
confidence: 99%
“…First, when its value is held constant the process can always be operated within feasible region at a minimum cost e.g. minimum compressor duty [10]. Second, this variable is insensitive to unmeasured disturbances and third, variations in its set-point will not affect the cost function significantly [11].…”
Section: Optimizing Controlled Variablementioning
confidence: 99%
“…The difference between the condensation and evaporation temperature in a simple refrigeration cycle is considered as the dominant factor in the relationship between heat transfer and compressor work [14]. Also it was reported that for propane precooled mixed refrigerant (C 3 MR) liquefaction process, the difference temperature between inlet and outlet of MR is discovered to be the proper optimizing controlled variable [10].…”
Section: Optimizing Controlled Variablementioning
confidence: 99%
“…Moreover, the total energy consumption of the system will be reduced through the combination of steady and dynamic optimization using dynamic simulation 27 . But there exists a shortage of comprehensive and systematic research for multi-factor coupling energy-saving optimization, such as a variety of dynamic control structure optimization analysis [28][29][30] and multiple variables optimization 31 .…”
Section: Introductionmentioning
confidence: 99%